1998
DOI: 10.1002/(sici)1097-4601(1998)30:8<523::aid-kin1>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the ligand substitution on the trimethylplatinum(iv) complexes with unidentate ligands

Abstract: Conditional pseudo-first-order rate constant k 0 increased linearly with the k /k ϭ 12.0 Ϯ 0.3. Ϫ1 2 concentration of NaY, while it decreased drastically with the concentration of NaX. Some plausible mechanisms were examined, and the following mechanism was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…An increase of the temperature to the maximum possible for the solvents used indicated the presence of a dynamic process with free sulfide, as expected for the rate constant found for its interchange (see below). 2D 1 H NOESY experiments have already indicated that this process includes the interchange of the two platinum-bonded methyl groups via a turnstile twist process that stops when the less labile phosphine derivative is considered or when the temperature is decreased. 5a, Nevertheless, even when the temperature is decreased, no better 1 H NMR signals are obtained; Figure is representative for the spectra obtained for these situations.
1 Variable-temperature 1 H NMR in the SMe 2 region for the compound dFMe in the presence of free dimethyl sulfide ligand.
…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…An increase of the temperature to the maximum possible for the solvents used indicated the presence of a dynamic process with free sulfide, as expected for the rate constant found for its interchange (see below). 2D 1 H NOESY experiments have already indicated that this process includes the interchange of the two platinum-bonded methyl groups via a turnstile twist process that stops when the less labile phosphine derivative is considered or when the temperature is decreased. 5a, Nevertheless, even when the temperature is decreased, no better 1 H NMR signals are obtained; Figure is representative for the spectra obtained for these situations.
1 Variable-temperature 1 H NMR in the SMe 2 region for the compound dFMe in the presence of free dimethyl sulfide ligand.
…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the introduction of very good σ donors on the coordination sphere should lead to an increase in the metal electron density that could produce an increase of its lability . Consequently, it is not strange that the introduction of Pt−C bonds in Pt(IV) t 2g 6 complexes leads to an important lability increase in their substitution reactions, and that they tend to operate through a dissociatively activated mechanism …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the interchange of the methyl groups in oxidative addition reactions of MeI in this type of complexes has already suggested its fast substitution reactivity. Recent kinetic studies have also confirmed that dimethyl sulfide substitution reaction rates are quite fast 1 …”
Section: Introductionmentioning
confidence: 93%